Synthesis of allenes by 1,2-elimination - Armstrong, RJ (Bentham Science Publishers, 2019)
Allenes represent an extremely important class of organic molecules, which, as a result of their twisted orthogonal π-systems can possess axial chirality. A wide array of methods for allene synthesis have been reported, such as the substitution of propargylic electrophiles, isomerization of alkynes and sigmatropic rearrangement. An alternative approach for the synthesis of allenes is 1,2-elimination of an appropriately substituted precursor. This mini-review highlights recent examples of 1,2-elimination processes, which target allenes including both polar and radical processes. The main focus is upon how control over the stereospecificity (e.g. syn- or anti-) of the 1,2-elimination process can enable the synthesis of enantioenriched axially chiral allenes. Recent developments in this field are presented including both enantiospecific and catalytic asymmetric methods.